2019
DOI: 10.1177/0363546519892916
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lumbosacral Spine Pathology on Minimum 2-Year Outcome After Hip Arthroscopy: A Nested Case-Control Analysis

Abstract: Background: Previous literature has examined the association between lumbosacral pathology and hip pathomechanics. However, the effect of lumbosacral pathologies and previous lumbosacral surgery on achieving meaningful outcomes after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) has yet to be studied conclusively. Purpose: To determine whether a history of lumbosacral spine pathology has an influence on achieving minimal clinically important differences (MCIDs) after hip arthroscopy for FAIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…pathology, although it is important to note that patients did significantly improve from their preoperative baseline, nevertheless. 15,16 Given the evidence that spine pathology causing decreased motion results in potentially inferior outcomes following hip arthroscopy, it follows that anatomic variants that alter spinopelvic mechanics may have similar effects. Luo, Barsoum, Ashraf, Cheng, Hurwitz, Goldsmith, and Moley help advance our understanding of the complex relationship between lumbosacral anatomy and mechanics and hip outcomes with their study in the current issue, "Prevalence of Lumbosacral Transitional Vertebrae in Patients With Symptomatic Femoroacetabular Impingement Requiring Hip Arthroscopy."…”
Section: See Related Article On Page 149mentioning
confidence: 99%
“…pathology, although it is important to note that patients did significantly improve from their preoperative baseline, nevertheless. 15,16 Given the evidence that spine pathology causing decreased motion results in potentially inferior outcomes following hip arthroscopy, it follows that anatomic variants that alter spinopelvic mechanics may have similar effects. Luo, Barsoum, Ashraf, Cheng, Hurwitz, Goldsmith, and Moley help advance our understanding of the complex relationship between lumbosacral anatomy and mechanics and hip outcomes with their study in the current issue, "Prevalence of Lumbosacral Transitional Vertebrae in Patients With Symptomatic Femoroacetabular Impingement Requiring Hip Arthroscopy."…”
Section: See Related Article On Page 149mentioning
confidence: 99%
“…As the authors pointed out, this is demonstrated in our current study as well as in previous studies evaluating the effect of spinal disorders on outcomes after addressing hip pathology. [1][2][3]5 Additionally, our team has also published a number of studies that have indicated improvements in functional outcomes after undergoing hip arthroscopy in patients with multiple joint pathologies, including spine, 4 after surgical treatment of gluteus medius tear in patients with spinopelvic deformities and after arthroscopic correction of femoroacetabular impingement syndrome (FAIS) in patients with sacroiliac joint abnormalities. It is important to note, however, that the studies mentioned above comparing functional scores between patients with spine aberration and those without a history of spinal disorders all demonstrate lower functional score averages in the spinal pathology group.…”
Section: Dear Editormentioning
confidence: 99%
“…Recently, we read the article entitled ''The Influence of Lumbosacral Spine Pathology on Minimum 2-Year Outcome After Hip Arthroscopy: A Nested Case-Control Analysis'' by Beck et al 1 They found that compared with the no lumbosacral pathology group, the lumbosacral pathology group achieved significantly worse short-term meaningful clinical outcomes after undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS). We appreciate the work that has been done by the authors and think this finding is of value for clinicians in decision-making.…”
Section: Dear Editormentioning
confidence: 99%